SEKOLAH PENDIDIKAN KARAKTER DI KABUPATEN GOWA DENGAN KONSEP ARSITEKTUR EKOLOGIS - Rasdyana, Rasdyana; Rahman, Sitti Aisyah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
The problem of education in Indonesia tend to be oriented to the education-based hard skills (technical skills), which is more developed the intelligence quotient (IQ) or just smart in the intellectual sense, and reasoning alone, not combined with intensive development of the heart's intelligence, feelings, and emotions soft skill or ability as stated in emotional Intelligence (EQ) and spiritual Intelligence (SQ). The purpose of this report is to draw up a reference design that can be a guide in designing the School of Architecture concept Ecological effective and efficient hereinafter ready transformed into the physical design of the building program. Results of this report reviews the specifics of the building, such as the terms of the planning involved, the concept footprint, appearance / shape of the building, space layout, structures, building materials, uilitas building with analyzing the problems and the potential that exists in the footprint based Ecological Architecture principles.